Assembled Optimized Design and Analysis of Prefabricated Pipe Piles. Issue 2 (April 2019) - Han, Na; Cheng, Bo; Song, Shuangyang; Sun, Jiandong; Zhang, Zhanhua; Liu, Zhaorui; Wu, Yongchun
Abstract: Prefabricated prefabricated pipe piles are major changes in pipe piles. They are characterized by standardized design, factory production, assembly construction, information management, and intelligent application, which are conducive to saving resources and energy, reducing construction pollution, and improving labor productivity and quality. The level of safety is conducive to promoting the deep integration of construction industry and information industrialization, cultivating new kinetic energy of new industries. It is an important measure for the transformation of new and old kinetic energy in the construction field and the promotion of construction methods. It is in line with the national green, circular and low-carbon sustainable development direction. This paper verifies the tube with ten pin connectors and eight pin connectors in the prefabricated pipe pile assembly connection process by comparing the test data of ten pin connector and eight pin connector structural performance tests. The structural bearing capacity of the pile joints is basically the same, and does not affect the structural performance of the prefabricated pipe piles in the normal use stage. In this way, the amount of steel is reduced, the engineering cost is reduced, and the construction period is shortened.